WAVE PROPERTIES AND FOCAL MECHANISMS OF N-TYPE EARTHQUAKES AT ASAMA VOLCANO - Aoyama H.; Takeo M. (My University, 2001)
N-type earthquakes sometimes occur before the eruption of andesitic volcanoes, but their source mechanism has not been understood well. Their waveforms have stationary periods and decay slowly resembling to damped oscillation. They have common characteristics of spectra among the different stations; these spectral peaks appear at almost equal intervals of 1.0Hz with common sharpness. We made detailed analysis on the N-type earthquakes observed at Asama volcano in July 1995. During 10days activity, the duration of each earthquake increased gradually from 40s to 3min, while the peak frequency decreased from 2.7 to 0.8Hz. Hypocenters are distributed slightly west under the summit crater with 0.4-1.7km above sea-level. Source mechanism of the N-type earthquake is determined using a waveform inversion technique. Synthetic waveforms are calculated using 2D finite difference method. Surface topography is included in the calculation to incorporate the case that the source region is higher than the stations. Since the optimum solution has a large volumetric component, we approximated the volumetric part as a volume change of fluid filled sphere or cylinder or plane crack, and decomposed the solution into volumetric and non-volumetric part. Consequently, it is revealed that the optimum solution can be expressed as ''crack expansion (contraction)+small fault slip'', because the spectral peak distribution advocates the crack expansion model among these three candidates. The frequency change during this activity may be explained by the time variation of the sound speed of inner fluid from 300 to 100m/s. The change of the void fraction of water-steam phase might have caused the decrease of the sound speed.
Keywords: VOLCANIC EARTHQUAKE; SOURCE MECHANISM; WAVEFORM INVERSION; FLUID FILLED CRACK